Screening of Premature Infants for Retinopathy of Prematurity in a Tertiary Eye Hospital (Central Medical College Journal, 2025)
Background: Retinopathy of prematurity (ROP) is a proliferative retinopathy affecting premature infants of very low birth weight, who have been exposed to high ambient oxygen concentrations; and is a leading cause of childhood blindness. The population of infants at risk for retinopathy of prematurity (ROP) varies by world region; in countries with well-developed neonatal intensive care services, the highest risk infants are those born at less than 28 weeks gestational age (GA) and less than 1 kg at birth, while, in regions where many aspects of neonatal intensive and ophthalmological care are not routinely available, more mature infants up to 2000 g at birth and 37 weeks GA are also at risk for severe ROP. Aim of the study was to evaluate the profile of ROP in a tertiary level eye hospital in Bangladesh. Method: Descriptive study was conducted from 1st January 2023 to 31st December 2023. A total of 72 premature infants irrespective of gestational age, gender & body weight were examined in this hospital for evaluation of ROP. Prior to commencement of this study, the study protocol was approved by the ethical review committee. Written informed consent was ensured from every parents of each of the participants. All patients were examined by single senior pediatric ophthalmologist with indirect ophthalmoscope after dilatation of pupil. Data collection was done through a structured form with the variables of gestational age (GA), gender body weight (BW) and duration of oxygen inhalation (O2) & neonatal intensive care unit (NICU). After collection of all the required data, analysis was done by Microsoft Excel. Result: Among 72 patients 42 were male and 30 were female. Six patients (8.3%) were found with gestational age less than 28 weeks. Gestational age 28 to 32 weeks was observed in 34 (47.2%) patients; and gestational age >38 weeks was found in only 4 (5.5%) patients. In this study mean gestational age of the patients was found 32.45 weeks. Body weight at birth 2 kg body weight was 10 (13.9%) patients. Out of 72 patients various grade of ROP was diagnosed in 32 (44.5%) babies; among them only 6 (8.3%) patients was selected as need treatment and rest 26 (36.1%) was advised for follow-up in different schedule. Conclusion: About half of the patients (44.5%) attending for ROP screening in this institute develops ROP. That is an alarming sing for the community and deserving attention to examine the premature babies in terms of gestational age, body weight and oxygen (O2) use in NICU.Central Medical College Journal Vol 8 No 2 July 2024 Page: 70-74